A New Simulation Method Providing Shock Mount Selection Assurance - Michael A. Talley; Shahram Sarkani (Shock and Vibration)
This paper presents the development and assessment of a practical and efficient process for assessing and/or designing shock isolation systems. This process combines practical methods for determining relative displacements and accelerations (e.g. shock response spectrum analysis) with a new, efficient, easy to use, 6 degree of freedom (6DOF) simulation method known as Shock Isolation Mount Predictions & Loading Estimates (SIMPLE). SIMPLE is also a tool that can easily account for uncertainties in isolated systems and their environments. The implementation of 6DOF rigid body theory in SIMPLE is validated by comparing simulation results with other analytical methods. This paper also summarizes assessments and designs for 60 different mounting systems using SIMPLE. In addition, experimental results from shock tests are compared with pre-test SIMPLE sensitivity simulations and with results of post-test model calibrations. These comparisons show the validity of: 1) using 6DOF analysis; 2) using statically derived load-deflection data for simulations; and 3) assessing and designing isolated systems using uncertainties in model parameters.